ANALISIS RISIKO KESEHATAN LINGKUNGAN PAPARAN NITROGEN DIOKSIDA (NO2) PADA PEDAGANG KAKI LIMA DI TERMINAL PULOGADUNG JAKARTA TIMUR - Annisa Amaliana; Yusniar Hanani Darundiati; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pulogadung bus station is one terminal with a solid transport activity and potentially contribute a lot of air pollution. Motorized transport will produce a variety of gases including NO2 which can cause  bad effect on health for example respiratory problems, throat irritation and eye irritation, especially for street vendors who almost 24 hours in the bus station.The purpose of this study was to analyze the risk of exposure to NO2 in Pulogadung Bus Station to transportation activities. The design study is an cross sectional approach of Environmental Health Risk Assessment (ARKL). The population of subject is140 street vendors in Pulogadung Bus Station and a population of object  is ambient air in Pulogadung Bus Station. Sample subjects were 60 vendors in Pulogadung Terminal and sample objects  the ambient air at four points around the Pulogadung Bus Station. Analysis of data using the steps in ARKL namely hazard identification, dose-response analysis, exposure analysis and risk characteristics.The results showed an average of NO2 concentration measurement results in Pulogadung Terminal in East Jakarta is 0.07141 mg / m3. While the average weight of street vendors in Pulogadung terminal in East Jakarta is 58.32 kg, with an average daily exposure time street vendors is 13 hours per day, the average frequency of exposure per year is 329 days per year and the average duration of exposure street vendors is 15 years old. The conclusion is the concentration of NO2 in Pulogadung Terminal is still below the quality standards established and the average exposure in real time and lifetime of street vendors in Pulogadung Bus Station is still under 1 and otherwise still safe. The calculation of risk estimates in Pulogadung Terminal vendors be at risk of non-cancer due to exposure to NO2 in the next 40 years. The suggestions in this study is street vendor should using PPE when working and reducing working hours.